Measaurement of the intelectual contribution of the issue: Synergetic effect of emotions on the travel motivation of senior tourists - Pestana, M.; Moutinho, L.; Philips, P. (Proceedings of the TMS Algarve 2016 – Tourism & Management Studies International Conference, 2016)
Detecting the signs of potential valuable ideas has theoretical and practical implications in order to safeguard the integrity of scientific knowledge. A critical part is to discern whether the study of a new idea is cognitively demanding. Not only do we need to have an up-do-date understanding of the scientific field’s intellectual structure as we must be able to identify exactly how the newly idea is connected to the intellectual structure as well. The perceived value of this paper is to provide specific trails of evidence to show why and how “The Synergetic Effect of Emotions on Travel Motivation of Senior Tourists” is novel in the scientific domain. The prediction of its potential value is going to be made in computational terms, using the program CiteSpace, showing the degree of changes introduced by it due to its connection with previously disparate patches of knowledge, creating a network of ideas. CiteSpace supports the modeling and visualization of our topic from bibliographical sources in terms of networks of several types of entities, including cited references, co-authors, co-occuring keywords and identify centrality between pivotal points as a measure of the importance of those nodes. This paper centered on document citations and co-citations networks in order to deliver accurate results for the knowledge of each domain. Individual nodes in the network can be aggregated into different thematic concentrations or clusters, based on their interconnectivity. Other points of interest include articles highly cited, strong bursts and hight frequency of occurance.